Developments in the design and microfabrication of photovoltaic retinal implants - Pratik Kusumanchi; Stephan Sylvest Keller; Rasmus Schmidt Davidsen (Micro and Nano Engineering)
Photovoltaic retinal implants are emerging as a promising technological solution for restoring vision for patients suffering from retinal degenerative diseases such as retinitis pigmentosa and age-related macular degeneration. These prostheses contain arrays of miniaturized solar cells converting light into electrical output signals, which subsequently are employed for local activation of the intact neuroretina via microelectrodes. Leveraging cutting-edge microfabrication techniques, photovoltaic retinal implants are compact and provide a high density of solar cell pixels. This potentially increases the resolution of the artificial vision and the field of view and lowers the threshold for stimulation of retinal neurons. The introduction of flexible substrates and the integration of 3D electrodes has greatly improved the connection with retinal neurons, optimizing the spatial resolution and potentially lowering the stimulation threshold. This review explores the latest developments in photovoltaic retinal prostheses, highlighting key aspects of their design, fabrication and performance. This field of research is still in its early stage and particular emphasis is laid on promising future research directions including miniaturization of pixels, incorporation of organic flexible semiconductors and first studies considering 3D stimulating electrode structures. Despite the significant progress made, there are still substantial challenges to overcome, such as ensuring long-term biocompatibility and validation of the novel concepts in clinical trials. Ongoing interdisciplinary research and development are essential for moving these promising technologies from the lab to real-world clinical applications, ultimately enhancing vision restoration. This review aims to provide a comprehensive overview of the current state of photovoltaic retinal implants and pinpoints critical areas for future research to further advance this transformative technology.